Yomida Hamadi's cenderawasih batik creations in Papua: study of motive forms, patterns and structures - Nathalia Dwijayanti; Bagus Indrayana (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The Cenderawasih Batik, created by Yomida Hamadi, is written as a repertoire of flora and fauna, which is a local cultural product as the motif. The depiction of batik's decorative components is through forming, patterning, and arranging the motifs, finally resulting in Cenderawasih batik. This study aims to describe the process of forming motifs, patterning techniques, and the process of composing batik motifs by Yomida Hamadi. It uses a research method of examining the motif's shape, pattern, and structure, which is a qualitative descriptive method supported by the theory of structural aesthetics to obtain a valid interpretation of objectivity. The result of the discussion of this study reveals the shape of the Cenderawasih batik motif as a work of art in arranging the motif's combination based on three decorative components, namely the main motif (Cenderawasih bird), the filler motif (areca nut), and the isen (betel nut) motif which is distilled in form. The batik modelling technique applies a combination of horizontal and vertical patterns and the Cenderawasih batik structure, with a combination of one motif with another to get a harmonious motif. The structure of the Cenderawasih batik motif is formed based on elements of art, made simple by paying attention to the elements of harmony, balance, contrast, unity, simplicity, accentuation, and proportion. The expectations achieved in this study may help identify and apply the process of forming motifs, patterning techniques, and making motifs by Yomida Hamadi. Hopefully, the community will better understand the process of creating creative batik whose motifs are inspired by the natural-cultural richness of the Land of Papua